Metagenomic surveillance and comparative genomic analysis of Chlamydia psittaci in patients with pneumonia - Huang, Weifeng; Hu, Shuqin; Zhu, Yongzhe; Liu, Shijia; Zhou, Xingya; Fang, Yuan; Lu, Yihan; Wang, Ruilan (Frontiers in Microbiology, 2023)
Chlamydia psittaci, a strictly intracellular bacterium, is an underestimated etiologic agent leading to infections in a broad range of animals and mild illness or pneumonia in humans. In this study, the metagenomes of bronchoalveolar lavage fluids from the patients with pneumonia were sequenced and highly abundant C. psittaci was found. The target-enriched metagenomic reads were recruited to reconstruct draft genomes with more than 99% completeness. Two C. psittaci strains from novel sequence types were detected and these were closely related to the animal-borne isolates derived from the lineages of ST43 and ST28, indicating the zoonotic transmissions of C. psittaci would benefit its prevalence worldwide. Comparative genomic analysis combined with public isolate genomes revealed that the pan-genome of C. psittaci possessed a more stable gene repertoire than those of other extracellular bacteria, with 90% of the genes per genome being conserved core genes. Furthermore, the evidence for significantly positive selection was identified in 20 virulence-associated gene products, particularly bacterial membrane-embedded proteins and type three secretion machines, which may play important roles in the pathogen-host interactions. This survey uncovered novel strains of C. psittaci causing pneumonia and the evolutionary analysis characterized prominent gene candidates involved in bacterial adaptation to immune pressures. The metagenomic approach is of significance to the surveillance of difficult-to-culture intracellular pathogens and the research into molecular epidemiology and evolutionary biology of C. psittaci.